1992
DOI: 10.1079/bjn19920012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fates of U-14C-labelled monosaccharides and an enzyme-treated cell-wall substrate in the fowl

Abstract: A major benefit of supplementing non-ruminant feedstuffs with exogenous enzymes is presumed to be the degradation of plant cell-wall polysaccharides to metabolizable monosaccharide residues. In the present study, metabolic fates of (U-'4C-labelled, 10 mM) glucose, galactose, mannose, xylose and arabinose were compared in the fowl, by measuring recoveries of 14C radioactivity in exhaled carbon dioxide, excreta and body tissues after administration either by wing vein (iv) or into the crop (ic). A further compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In chickens, Savory (1992) reported that d-xylose was absorbed slower than d-glucose and d-galactose but faster than d-arabinose and d-mannose, which concurs with results previously reported in chicks (Wagh and Waibel 1967), rats (Kohn et al 1965), and humans (Wood and Cahill 1963), suggesting that the absorption rates of these sugars may depend on their relative contributions of active and passive (transcellular and paracellular) transfer mechanisms (Savory 1992).…”
Section: Mechanism Of Sugar Absorptionsupporting
confidence: 81%
“…In chickens, Savory (1992) reported that d-xylose was absorbed slower than d-glucose and d-galactose but faster than d-arabinose and d-mannose, which concurs with results previously reported in chicks (Wagh and Waibel 1967), rats (Kohn et al 1965), and humans (Wood and Cahill 1963), suggesting that the absorption rates of these sugars may depend on their relative contributions of active and passive (transcellular and paracellular) transfer mechanisms (Savory 1992).…”
Section: Mechanism Of Sugar Absorptionsupporting
confidence: 81%
“…The findings in Fig. 3 suggest that some of this activity could still have been in contents of the hind-gut, but presumably most was in body tissues (recoveries of 14C from these sites were measured in other trials with U-14C-labelled cell-wall material reported elsewhere, Savory, 1992). The differences between dry and wet treatments in percentages of 14C recovered in excreta were almost entirely accounted for by differences in '*CO, production with spinach and Festuca, but not with cellulose (Table 4).…”
Section: -mentioning
confidence: 64%
“…None of the evidence thus obtained refutes the original assumption (p. 91) that '*CO, production can be used as an indicator of degradation and metabolism of U-'4C-labelled cell-wall substrates. In subsequent trials (Savory, 1992) the model was refined by using three bottles of CO, trapping solution instead of two, and by having nine collection periods, of either 50 or 60 min, instead of eight. With [U-'*C]cellulose the significant reduction in total 14C recovery in exhaled CO, with the antibiotic pretreatment, compared with the no-enzyme, dry control treatment (Table 3), appears to confirm that degradation of cellulose by intestinal microflora does occur…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the metabolizable energy was not due to complete hydrolysis of NSP by exogenous enzymes and subsequent absorption of the released sugars, but due to the significant increase in apparent pentosan digestibility (26 vs. 44%) and in ileal starch digestibility (88 vs. 98%). A potential contribution of the main cell-wall residues released by feed enzymes to the metabolizable energy in the fowl appear to be in the order: glucose > galactose > xylose > arabinose > galacturonic acid (Savory, 1992).…”
Section: The Effect Of Seed Processing On Dietary Fibre Utilisationmentioning
confidence: 99%